2004
DOI: 10.1002/art.20531
|View full text |Cite
|
Sign up to set email alerts
|

Differences between participants and nonparticipants in an exercise trial for adults with rheumatoid arthritis

Abstract: Objective. To investigate the generalizability of the results of a randomized controlled trial on the effectiveness of long-term, high-intensity exercises in the rheumatoid arthritis patients in training (RAPIT) trial by comparing the characteristics of the participants with the nonparticipants. Methods. Participants and nonparticipants were mailed questionnaires on sociodemographic characteristics, health status, reasons not to participate, and attitudes toward intensive exercise. Results. The questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
4
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 34 publications
2
46
4
4
Order By: Relevance
“…However, only three studies reported the average age of participants as falling within the fifth and sixth decades, and none in the seventh decade. This may reflect other observations that participants in PA trials tend to be younger 44,45 .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, only three studies reported the average age of participants as falling within the fifth and sixth decades, and none in the seventh decade. This may reflect other observations that participants in PA trials tend to be younger 44,45 .…”
Section: Discussionmentioning
confidence: 56%
“…These reasons have been cited in other PA trials in RA 44,45 . An in-depth analysis of participants and nonparticipants in a recent PA trial in RA concluded that only 8% of the initial target population…”
Section: Discussionmentioning
confidence: 71%
“…In total, the approximate number of RA patients treated in 2005 and/or 2006 in the 11 centers was 9,830. Assuming that 75% of the patients would be eligible for participation in this exercise program (12), with 150 of 7,372 participants, 2.0% of the target population was reached (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…For this information, the head of the department of rheumatology in each of the centers estimated the total number of patients with RA, preferably based on hospital registries. From the RAPIT study, it is known that 600 (25%) of 2,426 patients with RA were not eligible because of weightbearing prostheses or comorbidity (12). To estimate the magnitude of the target population, we therefore considered 75% of all RA patients eligible for participation in the RAPIT program.…”
mentioning
confidence: 99%
“…Physiologic loading of the cartilage tissue is required to maintain tissue homeostasis, while non-physiologic loading (disuse and overuse) promotes its degradation (Sun 2010). Intensive dynamic and weightbearing exercises were originally considered detrimental for patients with RA due to concerns of exacerbating disease, (van den Ende et al 1996), but studies have shown such exercise does not cause an increase in the rate of damage to either large (de Jong et al 2003) or small joints (de Jong et al 2004). There were no significant differences in the rate of damage of large joints 18 months following the end of a high-intensity program between RA patients who discontinued exercise and those who were still exercising (de Jong et al 2009).…”
Section: Anti-catabolic Effects Of Exercise On Cartilagementioning
confidence: 99%